The Acculturation of Batik Lasem’s Culture With Chinese Motif in the 18th to 20th Century - Vera Jenny Basiroen (Institut Seni Indonesia Denpasar, 2019)
Batik Lasem is one of the famous heritages in Indonesia. Lasem has a unique batik motif because it is a blend of Chinese and Javanese culture, which results in a combination of motifs with distinctive shapes and colors, as well as having motifs that are full of meaning. The city of Lasem was chosen because it plays an important role as a batik producer in Indonesia, which is bought by Chinese culture. The purpose of this research is to study and analyze the variety of Chinese decoration in Lasem and its development in the 18th century until the 20th century. The research method used is the study of literature, while the theory used is cultural acculturation theory and discussion of the theory from previous research.